Implementation of a Peer HIV Community Support Worker Program in Rural Ethiopia to Promote Retention in Care - Alan R. Lifson MD, MPH; Sale Workneh MD; Abera Hailemichael MS; Workneh Demisse MPH; Lucy Slater MPH; Tibebe Shenie MBA (Journal of the International Association of Providers of AIDS Care, 2017)
Retention in care is a major challenge for HIV treatment programs, including in rural and in resource-limited settings. To help reduce loss to follow-up (LTFU) for HIV-infected patients new to care in rural Ethiopia, 142 patients were assigned 1 of 13 trained community health support workers (CHSWs) who were HIV positive and from the same neighborhood/village. The CHSWs provided HIV and health education, counseling/social support, and facilitated communication with the HIV clinics. With 7 deaths and 3 transfers, the 12-month retention rate was 94% (95% CI = 89%-97%), and no client was LTFU in the project. Between enrollment and 12 months, clients had significant ( P ≤ .001) improvements in HIV knowledge (17% increase), physical and mental quality of life (81% and 21% increase), internalized stigma (97% decrease), and perceived social support (24% increase). In rural and resource-limited settings, community-based CHSW programs can complement facility-based care in reducing LTFU and improving positive outcomes for HIV-infected people who enter care.